2010
DOI: 10.1002/uog.7560
|View full text |Cite
|
Sign up to set email alerts
|

Sonographic appearance of gestational trophoblastic disease evolving into epithelioid trophoblastic tumor

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 12 publications
2
16
0
Order By: Relevance
“…Four cases among five previous reports exhibited cystic components within lesions on radiological images . The ETT in our case did not show cystic components within the lesion on CT and MR images.…”
Section: Discussionsupporting
confidence: 47%
See 1 more Smart Citation
“…Four cases among five previous reports exhibited cystic components within lesions on radiological images . The ETT in our case did not show cystic components within the lesion on CT and MR images.…”
Section: Discussionsupporting
confidence: 47%
“…Four cases among five previous reports exhibited cystic components within lesions on radiological images. 4,[6][7][8][9] The ETT in our case did not show cystic components within the lesion on CT and MR images. Kageyama et al reported that the cystic component contained massive amounts of necrotic tissue and hemorrhagic materials, and no cystic wall was present.…”
Section: Figuresupporting
confidence: 41%
“…Radiologically, these tumors are well-circumscribed. Doppler ultrasound has demonstrated an increase in blood flow [2,19,20]. …”
Section: Discussionmentioning
confidence: 99%
“…• Epithelioid trophoblastic tumor appear early in the course of disease with irregular echolucent lacunae within the myometrium on transvaginal ultrasound, but later in the disease with a well-circumscribed solitary echogenic lesion in the fundal myometrium without blood fl ow [ 50 ]. …”
Section: Ultrasound In the Diagnosis And Management Of Gtnmentioning
confidence: 98%